Empathy between embodiment and digital depersonalization - Simonič, Barbara (Poligrafi, 2025)
Empathy, the ability to understand and share the experience of another, is tra-ditionally understood as a cornerstone of interpersonal relationships and social cohesion. However, in the age of digital communication and the increasing virtu-alization of interactions, important questions arise about the nature, expression, and impact of empathy. The development of digital technology and the ubiquity of the internet are changing the way we interact and communicate with each other, with the physical aspect increasingly disappearing. although digital tools allow us to make contact quickly and efficiently, concerns are being raised about the impact of these forms of communication on the quality of interpersonal relationships. Digital communication is often text-based, asynchronous, and often anonymous, which reduces the presence of physical and social signs that are essential for a clas-sic empathic experience. against this backdrop, the discussion of empathy in the context of digital depersonalization requires a holistic approach that encompasses philosophical, psychological, and other perspectives. in this paper, we will address the challenges of empathy based on physicality and direct interpersonal contact, which are often diminished or absent in digital communication. This absence re-duces the possibility of a full empathic experience and promotes the phenomenon of depersonalization.
Keywords: depersonaliizacija; depersonalization; digital communication; digitalno sporazumevanje; embodiment; empathy; empatija; interpersonal relationships; medosebni odnosi; utelešenost